A National Survey of Public Awareness of the Environmental Impact and Management of CCUS Technology in China. (July 2017) - Li, Qi; Liu, Guizhen; Leamon, Gregory; Liu, Lan-Cui; Cai, Bofeng; Chen, Zheng-Ao
Abstract: Carbon dioxide capture, utilization and geological storage (CCUS) is regarded as an important option for climate change mitigation. China is also undertaking a series of actions for emissions reduction with paying much attention to the CCUS technology. In order to better promote the deployment and development of CCUS projects from the perspective of environmental management in China, a national survey was conducted to investigate the public awareness and understanding of the environmental impact and management of CCUS technology. The key findings of the survey can be concluded as follows: (1) CCUS technology itself shows some favorable environmental benefits, but awareness of high environmental risks lowers public acceptance; (2) The government departments with high expectations to play a key role in environmental management; (3) Information about CCUS projects on traditional and electronic media, or from expert lectures and government departments can lower the perceived risk and improve the public acceptance of CCUS.